2015
DOI: 10.1089/brain.2013.0186
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Medial Prefrontal–Subcortical Connectivity in Dysphoria: Granger Causality Analyses of Rapid Functional Magnetic Resonance Imaging

Abstract: A cortico-limbic network consisting of the amygdala, medial prefrontal cortex (mPFC), and ventral striatum (vSTR) has been associated with altered function in emotional disorders. Here we used rapidly sampled functional magnetic resonance imaging and Granger causality analyses to assess the directional connectivity between these brain structures in a sample of healthy and age-matched participants endorsing moderate to severe depressive symptomatology as they viewed a series of natural scene stimuli varying sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Over the last years, GC analysis (Granger, 1969 ) has been applied in several studies, mainly in fMRI (see e.g., Roebroeck et al, 2005 ; Rypma et al, 2006 ; Sridharan et al, 2008 ; Florin et al, 2010 ; Gao et al, 2011 ; Hamilton et al, 2011 ; Liao et al, 2011 ; Miao et al, 2011 ; Zhou et al, 2011 ; Al-Aidroos et al, 2012 ; Tang et al, 2012 ; Wen et al, 2012 ; Wu et al, 2013 ; Zhang and Li, 2013 ; Sabatinelli et al, 2014 ; Yang and Shu, 2014 ) and (considerably fewer) in EEG (Chávez et al, 2003 ; Hesse et al, 2003 ; Gow et al, 2008 ; Keil et al, 2009 ; Dauwels et al, 2010 ; Barnett and Seth, 2011 ; Barrett et al, 2012 ; Nicolaou et al, 2012 ; de Tommaso et al, 2013 ; Wu et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…Over the last years, GC analysis (Granger, 1969 ) has been applied in several studies, mainly in fMRI (see e.g., Roebroeck et al, 2005 ; Rypma et al, 2006 ; Sridharan et al, 2008 ; Florin et al, 2010 ; Gao et al, 2011 ; Hamilton et al, 2011 ; Liao et al, 2011 ; Miao et al, 2011 ; Zhou et al, 2011 ; Al-Aidroos et al, 2012 ; Tang et al, 2012 ; Wen et al, 2012 ; Wu et al, 2013 ; Zhang and Li, 2013 ; Sabatinelli et al, 2014 ; Yang and Shu, 2014 ) and (considerably fewer) in EEG (Chávez et al, 2003 ; Hesse et al, 2003 ; Gow et al, 2008 ; Keil et al, 2009 ; Dauwels et al, 2010 ; Barnett and Seth, 2011 ; Barrett et al, 2012 ; Nicolaou et al, 2012 ; de Tommaso et al, 2013 ; Wu et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the movie condition of our experiment the dialog was represented with natural speech. A previous fMRI study by Moreno et al [ 42 ] employing natural and scrambled speech stimulus have revealed BOLD signal decrease in the precuneus, PHG, middle and inferior frontal gyri and parietal inferior lobule during natural speech comprehension. IC1 encompasses those regions and might therefore reflect its involvement in the comprehension of the natural speech (for movie dialogues) and imagery of the natural speech (for written dialogues).…”
Section: Narrative Network and Comparison With Previous Workmentioning
confidence: 99%
“…More precisely, the vmPFC shows increased activation patterns specifically for stimuli with pleasant content in comparison to unpleasant or neutral stimuli [3][4][5][6][7][8]. Furthermore, several psychiatric disorders were shown to be linked-amongst others-to dysfunctional processing in vmPFC regions [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%